Evaluation of Myelosupression during Imatinib Mesylate Therapy in Patients with Chronic Myeloid Leukaemia (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction:Chronic Myloid Leukaemia (CML) is a myeloproliferative neoplasm that originates in an abnormal pluripotent stem cell. Imatinib, a tyrosine kinase inhibitor, is the drug of choice for CML in the present time. During therapy, a few patients develop myelosuppression and present with cytopenias.Objectives: To evaluate myelosupression during therapy with Imatinib mesylate in patients with Chronic myloid leukaemia in chronic phase.Materials and Methods: This cross sectional observational study was carried out at department of Haematology, Combined Military Hospital, Dhaka and Haematology OPD, Bangabandhu Sheikh Mujib Medical University (BSMMU) from October 2011 to September 2012. A total of 30 patients fulfilling the inclusion criteria were included in this study. Data were collected in a structured proforma, analyzed with SPSS and expressed in mean, frequency and percentage.Results: Patients mean age was 38.96±9.37 years ranging from 23 to 56 years. Among 30 study subjects, male and female patients were 22(73%) and 08(27%) respectively. Most of the patients presented with generalized weakness (83.3%), weight loss (53.3%), fever (26.7%), pain abdomen (36.6%) and fullness of abdomen (33.3%). Twenty (66.67%) cases develop anaemia, 02(10%) cases leucopenia, 07(23.33%) cases thrombocytopenia and 11(36.6%) patients develop different combination of bicytopenia and 2% patients developed pancytopenia after being treated with Imatinib.Conclusion:   Various degrees of myelosupression with cytopenias may occur in few patients of CML on Imatinib therapy. Regular hematologic follow-up is required so that the drug may be stopped or dose modified as per the individual’s needs.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 189-192